TRANSITION FROM FOSSIL FUELS TO RENEWABLE ENERGY: APLLICATION OF OCEAN ENERGY TO POWER ELECTRICAL GRID IN SARAWAK, MALAYSIA. - Latif, Syahril Hidayat; Chew, Boon Cheong; Salleh, NurFarahin (Journal of Technology Management and Business, 2016)
Oceans cover more than 70% of the earth's surface. Therefore, the mechanical energy from the tides and waves is one of the most exciting areas of untapped energy potential. Application of ocean energy complements the fossil energy to power an electrical grid. The objective of this study was to investigate how the ocean energy could be applied as one of the main sources to power an electrical grid. Sarawak has been selected as a location to generate ocean energy because the geographical advantage of South China Sea and its wide-opening. A mixed method was utilized comprised a survey among the residents of Sarawak and a case study in High Institutions to understand the technical feasibility of this ocean technology. Ocean energy was found to have an enormous potential to generate energy to power the electrical grid in Sarawak. This technology could be introduced to Kuching, Sarawak to reduce the use of fossil as a source of electricity generation.Â